2017
DOI: 10.3233/npm-1642
|View full text |Cite
|
Sign up to set email alerts
|

Optimal radiologic position of an umbilical venous catheter tip as determined by echocardiography in very low birth weight newborns

Abstract: In VLBW newborns, placement of the UVC tip into the cRA or TIVC-RA junction by X-ray does not avoid misplacement in the left atrium as demonstrated by echocardiography. For VLBW infants, it is suggested that echocardiography may be helpful in verifying that the original placement or migration of the UVC tip into the LA has not occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…There is limited data demonstrating that US is superior for determining the position of the UVC when compared to CXR [10, 12, 13, 18, 24, 25]. Although other authors report poor correlation between the thoracic level by CXR and catheter location by US [10, 12, 13, 18, 24, 25], we found agreement between CXR and US in 23/30 imaging pairs. However, comparison of US and CXR in determining the UVC position was not the primary goal of this study, and conclusions about the accuracy of both modalities cannot be drawn.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…There is limited data demonstrating that US is superior for determining the position of the UVC when compared to CXR [10, 12, 13, 18, 24, 25]. Although other authors report poor correlation between the thoracic level by CXR and catheter location by US [10, 12, 13, 18, 24, 25], we found agreement between CXR and US in 23/30 imaging pairs. However, comparison of US and CXR in determining the UVC position was not the primary goal of this study, and conclusions about the accuracy of both modalities cannot be drawn.…”
Section: Discussionmentioning
confidence: 42%
“…In only 1/40 infants we could not visualize the UVC tip by US. To improve the detection of migration and malposition of UVCs, US is a valuable and feasible tool, as it mostly takes only a few minutes and avoids additional exposure to radiation [17, 24]. Our study showed that inadvertent migration occurs frequently between the placement of the UVC and Day 3.…”
Section: Discussionmentioning
confidence: 81%
“…We described 12 cases where the UVC tip was in the heart despite reassuring X‐ray findings, 3 within the LA (2%) and 13 within the RA (9%), demonstrating that determination of UVC tip position by vertebral level on X‐ray alone is problematic. This poor correlation between X‐ray vertebral position and CPU position has previously been shown by others . In a study of 65 extremely low birthweight neonates, Franta et al .…”
Section: Discussionmentioning
confidence: 70%
“…demonstrated LA and RA malposition at a rate of 45% (24) and 28% (15), respectively. Karber et al . noted a rate of 41% (21) of UVCs in the LA in a study of 51 extremely low birthweight neonates despite adequate position on X‐ray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation